Implementation Of The Semi Fowler Position To Improve The Effectiveness Of Breathing Patterns In Congestive Heart Failure (CHF) Patients At Vita Insani Pematangsiantar Hospital - Sihombing, Heny Indriyani; Lismawati, Lismawati (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Congestive Heart Failure (CHF) or called congestive heart failure where the heart is unable to pump enough blood to the human body's organs and other tissues. Symptoms that usually appear in sufferers of Congestive Heart Failure (CHF) are shortness of breath, weakness and fatigue, swollen ankles or stomach due to fluid buildup, increased respiratory frequency. The non-pharmacological action taken for Congestive Heart Failure (CHF) patients is giving the semi-Fowler position. This research design uses a case study method with 2 respondents through interviews and physical examination. The results of the study showed that after the nursing action was carried out, Mrs. N and Mr. A found a decrease in respiratory frequency in Mrs. N 27x/minute becomes 20x/minute while in Mr. A 24 x/minute becomes 20 x/minute. The action of providing a semi-fowler position to improve the effectiveness of breathing patterns in sufferers of Congestive Heart Failure (CHF)